2016
DOI: 10.1145/2872278
|View full text |Cite
|
Sign up to set email alerts
|

The MIT Museum Glassware Prototype

Abstract: With the growth of enthusiasm for the adoption of wearable technology in everyday life, the museum world has also become interested in understanding whether and how to employ smart glasses to engage visitors with new interpretative experiences. The growing interest in wearable technology encourages experimentation with smart glasses, as this trend is going to influence digital media interpretation for museums in the near future. To explore the use of smart glasses in the museum, a Glassware prototype was desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…the pickpocket or the juggler, have proved very effective in bringing together historical rigour and entertainment (Poole 2018) whilst the reuse of content intended for different devices may diminish the experience (e.g. text from panels, video clips from screens, and narratives from audio-guides were less than ideal on smart glasses (Mason 2016, Archeomatica 2016). The crafting of new narratives that fit the new use is key to a sustained enjoyment of the experience, particularly when the visual reconstruction for a place is a repetition of or similar to what has been seen before: to find new stories gives purpose to the visual exploration of the 3D reconstruction.…”
Section: Discussion and Guidelinesmentioning
confidence: 99%
“…the pickpocket or the juggler, have proved very effective in bringing together historical rigour and entertainment (Poole 2018) whilst the reuse of content intended for different devices may diminish the experience (e.g. text from panels, video clips from screens, and narratives from audio-guides were less than ideal on smart glasses (Mason 2016, Archeomatica 2016). The crafting of new narratives that fit the new use is key to a sustained enjoyment of the experience, particularly when the visual reconstruction for a place is a repetition of or similar to what has been seen before: to find new stories gives purpose to the visual exploration of the 3D reconstruction.…”
Section: Discussion and Guidelinesmentioning
confidence: 99%
“…The difference of using an AR headset to using the mobile is the opportunity and potential for full body interaction, since the hands are not engaged (Vainstein, Tsvi & Joel, 2016). Looking through a headset while not losing the view of the physical environment and being able to have the hands free is a more immersive experience than using the mobile (Mason, 2016). In addition, the experience design can make use of a variety of sensorial input, such as eye tracking and voice, to enable further interaction mechanisms that may be more natural to visitors of all ages.…”
Section: Smart Glass Ar Experiencesmentioning
confidence: 99%
“…In addition, the experience design can make use of a variety of sensorial input, such as eye tracking and voice, to enable further interaction mechanisms that may be more natural to visitors of all ages. The majority of research on AR headsets have so far focused on areas of science and ergonomics (Mason 2016;Mokatren 2018, Vainstein 2016Kerr 2011) such as navigation to a target location, situational awareness, and augmented imagery visibility. At the same time, an increasing number of applications are being designed for different contexts, and indoor and outdoor cultural heritage sites have been a fruitful ground for research and experimentation with AR.…”
Section: Smart Glass Ar Experiencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Since then, Sony, Microsoft, and Epson have also announced smart glasses [29]. Smart glasses are used in various fields including healthcare [30][31][32], training [33,34], logistics [35,36], and tourism [37,38], with many commercially available products. Detailed information on commercially available smart glasses have been reported by Syberfeldt et al [39], as shown in Table 1.…”
Section: Introductionmentioning
confidence: 99%